2019
DOI: 10.1002/cae.22187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parallel programming teaching methodologies: On‐campus versus online methodologies

Abstract: Contribution This study reveals that the programming paradigm is relevant to obtain advanced programming skills. Background Parallel computing has become mandatory for computer science students. The increasing amount of computational resources required by emerging applications need experienced programmers that fully exploit hardware resources. However, the hardware platforms and programming languages to leverage them evolve at a dizzying pace, making very challenging for students the successful learning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Based on the tested learning strategy, the researcher's analysis revealed no significant difference (p>0.05) in student accomplishment. The study's results supported past comparisons of the impacts of learning management system-assisted learning, which did not discover any appreciable distinctions between the experimental group and the traditional method (Adams & Dove, 2017;Al-Qahtani & Higgins, 2012;Bulut Ozek, 2018;Cantabella et al, 2019;Davis & Frederick, 2020;Jazayeri & Li, 2020;Vercellotti, 2017;Yorganci, 2020). Three schools made up the modest sample size of study participants in this investigation.…”
Section: Discussionsupporting
confidence: 76%
“…Based on the tested learning strategy, the researcher's analysis revealed no significant difference (p>0.05) in student accomplishment. The study's results supported past comparisons of the impacts of learning management system-assisted learning, which did not discover any appreciable distinctions between the experimental group and the traditional method (Adams & Dove, 2017;Al-Qahtani & Higgins, 2012;Bulut Ozek, 2018;Cantabella et al, 2019;Davis & Frederick, 2020;Jazayeri & Li, 2020;Vercellotti, 2017;Yorganci, 2020). Three schools made up the modest sample size of study participants in this investigation.…”
Section: Discussionsupporting
confidence: 76%
“…Typically, in traditional-based learning, students are able to interact directly with the lecturers and other students which allows prompt answers. It was also found that the number of students failing and dropping out of the course is higher in the online environment especially in the advanced programming course (Cantabella, 2020;Chimanga, 2021). Students preferred and felt that traditional lectures have better educational values than online-based as many showed disinterest and lack of motivation in commencing online-based learning because of the social isolation in the virtual lectures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies conducted by Cantabella (2020) and Maltby (2020) found that in online-based learning, there are limited interactions between the students and lecturers. This can be difficult and frustrating for the students in acquiring the programming language knowledge (Yagci, 2017) as there are delays in getting replies to their queries.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is necessary to indicate that interaction is highly complex (Duart Montoliu & Osorio Gómez, 2011) or a weakness in virtual education. In Spain, research was conducted on the evaluation of both faceto-face and online methodologies at university, concluding that interaction is the main problem between faculty and students in the virtual modality (Cantabella et al, 2020). Likewise, it is necessary that strategies are developed as part of the virtual methodology, in this way the teaching staff reaches an innovative level contributing to their professional work (Martínez-Garcés & Garcés-Fuenmayor, 2020).…”
Section: Introductionmentioning
confidence: 99%